2019
DOI: 10.1101/754069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

JUUL and Combusted Cigarettes Comparably Impair Endothelial Function

Abstract: Objectives JUUL and earlier generation electronic cigarettes (e-cigs) are promoted as being less hazardous than cigarettes. While JUUL Labs, in particular, claims that switching from smoking to vaping has beneficial impacts, the health effects of such products are not well understood. We investigated whether exposure to JUUL and previous generation e-cig aerosol impairs endothelial function comparably to cigarette smoke. Methods We exposed rats to aerosol from Virginia Tobacco flavor JUUL, an e-cig tank system… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…133 E-cigarettes are sometimes presented as a less-harmful alternative for nicotine-dependent tobacco smokers unwilling or unable to cease nicotine use, because the products deliver much lower levels of toxicants relative to cigarette smoke. 134,135 However, important concerns surrounding e-cigarettes include rising use prevalence among youth and young adults, 136 potential risks for cardiovascular and lung health, [137][138][139] and questions about cessation effectiveness outside clinical trials. The uncertainty and complexity of what impact widespread e-cigarette availability has had, and will have, on public health has spurred much controversy and policy debate.…”
Section: E-ci G Are T Te S and Other Novel Produc Tsmentioning
confidence: 99%
“…133 E-cigarettes are sometimes presented as a less-harmful alternative for nicotine-dependent tobacco smokers unwilling or unable to cease nicotine use, because the products deliver much lower levels of toxicants relative to cigarette smoke. 134,135 However, important concerns surrounding e-cigarettes include rising use prevalence among youth and young adults, 136 potential risks for cardiovascular and lung health, [137][138][139] and questions about cessation effectiveness outside clinical trials. The uncertainty and complexity of what impact widespread e-cigarette availability has had, and will have, on public health has spurred much controversy and policy debate.…”
Section: E-ci G Are T Te S and Other Novel Produc Tsmentioning
confidence: 99%
“…Previous studies identified several known flavor chemicals in JUUL e‐liquids that were potentially cytotoxic, including isopulegol, ethyl maltol, benzaldehyde, vanillin, benzyl alcohol, and pulegone (Omaiye, McWhirter, Luo, Pankow, & Talbot, 2019; Talih et al, 2019). Impaired endothelial function in rats following JUUL vape exposure has also been reported (Rao, Liu, & Springer, 2020). Here, we evaluated the effects of JUUL e‐liquids on two human cell lines, namely, HEK293T cells and M0 THP‐1 macrophage‐like cells.…”
Section: Discussionmentioning
confidence: 78%
“…7 As such, vaping during pregnancy may have a profound impact on vascular health and function and should not be considered "safe" or "risk-free." 8,9 In the weeks preceding this admission, the ECMO team had conducted a series of preparedness drills and drafted a checklist for managing suspected COVID-19 (Appendix 1). The drills involved multidisciplinary providers, nurses, perfusionists, respiratory therapists, security, and housekeeping in high-fidelity scenarios using mock pumps and mannequins in simulating transport, cannulation, and containment (Figure 2).…”
Section: Discussionmentioning
confidence: 99%